ANSWER
![( {36})^{ (- \frac{1}{2}) } = \frac{1}{6}](https://tex.z-dn.net/?f=%28%20%7B36%7D%29%5E%7B%20%28-%20%20%5Cfrac%7B1%7D%7B2%7D%29%20%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B6%7D%20)
EXPLANATION
The given expression is
![{36}^{( - \frac{1}{2} )}](https://tex.z-dn.net/?f=%20%7B36%7D%5E%7B%28%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20%29%7D%20)
This is having a negative index. We must first of all change to a positive index.
Recall that,
![{a}^{ - m} = \frac{1}{ {a}^{m} }](https://tex.z-dn.net/?f=%20%7Ba%7D%5E%7B%20-%20m%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B%20%7Ba%7D%5E%7Bm%7D%20%7D%20)
We apply this law of exponents to get,
![{36}^{( - \frac{1}{2} )} = \frac{1}{ {36}^{( \frac{1}{2} )} }](https://tex.z-dn.net/?f=%20%7B36%7D%5E%7B%28%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20%29%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B%20%7B36%7D%5E%7B%28%20%20%5Cfrac%7B1%7D%7B2%7D%20%29%7D%20%7D%20)
We cab rewrite the given expression to obtain;
![{36}^{( - \frac{1}{2} )} = \frac{1}{ \sqrt{36} }](https://tex.z-dn.net/?f=%20%7B36%7D%5E%7B%28%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20%29%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B%20%20%5Csqrt%7B36%7D%20%20%7D%20)
This will simplify to give us,
._ is the tenths place . Therefore the answer is 2.8
F(x) = x^2
g(x) = x^2+5
g(x) = f(x)+5
We see that g(x) is basically f(x) but we add on 5. So 5 will go in the blank.
- Let r represent Rick’s height.
- Therefore, the quotient of Rick’s height and 4
![= \frac{r}{4}](https://tex.z-dn.net/?f=%20%3D%20%20%5Cfrac%7Br%7D%7B4%7D%20)
- Fred is 5 inches shorter than the quotient of Rick’s height and 4.
- Therefore, an expression that represents Fred’s height is
![\frac{r}{4} - 5](https://tex.z-dn.net/?f=%20%5Cfrac%7Br%7D%7B4%7D%20-%205%20)
Answer:
![\frac{r}{4} - 5](https://tex.z-dn.net/?f=%20%20%5Cfrac%7Br%7D%7B4%7D%20-%205)
Hope you could get an idea from here.
Doubt clarification - use comment section.
here hope this helps!
Step-by-step explanation: